Virus adaptation to heparan sulfate comes with capsid stability tradeoff - Han Kang Tee; Simon Crouzet; Arunima Muliyil; Gregory Mathez; Valeria Cagno; Matteo Dal Peraro; Aleksandar Antanasijevic; Sophie Clément; Caroline Tapparel (eLife)
Because of high mutation rates, viruses constantly adapt to new environments. When propagated in cell lines, certain viruses acquire positively charged amino acids on their surface proteins, enabling them to utilize negatively charged heparan sulfate (HS) as an attachment receptor. In this study, we used enterovirus A71 (EV-A71) as the model and demonstrated that, unlike the parental MP4 variant, the cell-adapted strong HS-binder MP4-97R/167 G does not require acidification for uncoating and releases its genome in the neutral or weakly acidic environment of early endosomes. We experimentally confirmed that this pH-independent entry is not associated with the use of HS as an attachment receptor but rather with compromised capsid stability. We then extended these findings to another HS-dependent strain. In summary, our data indicate that the acquisition of capsid mutations conferring affinity for HS comes together with decreased capsid stability and allows EV-A71 to enter the cell via a pH-independent pathway. This pH-independent entry mechanism boosts viral replication in cell lines but may prove deleterious in vivo, especially for enteric viruses crossing the acidic gastric environment before reaching their primary replication site, the intestine. Our study thus provides new insight into the mechanisms underlying the in vivo attenuation of HS-binding EV-A71 strains. Not only are these viruses hindered in tissues rich in HS due to viral trapping, as generally accepted, but our research reveals that their diminished capsid stability further contributes to attenuation in vivo. This underscores the complex relationship between HS-binding, capsid stability, and viral fitness, where increased replication in cell lines coincides with attenuation in harsh in vivo environments like the gastrointestinal tract.